Estudio del comportamiento de un preparado enzimático (α-amilasa, β- amilasa y amiloglucosidasa) sobre masato semi-sólido de yuca (manihot esculenta crantz) para la obtención de una bebida. - Amagua González, Gina Sofía (2020)
The effect enzymatic addition cassava (Manihot esculenta CRANTZ) semi- solid masato reparation to obtain a drink was aimed at evaluating the behavior commercial enzymes behaviour at the production of cassava replacement by chewing process, process which was replaced with enzymes of different origin which are used to hydrolyze the carbohydrate molecules present in cassava starch making them simpler products such as monosaccharides and disaccharides making the cassava drink sweet and pleasantly flavoring. It was carried out on a methodology process for the cassava masato production of the different conditions after this process, the hydrolysis process was carried out with enzymes in which with a masato cassava dissolution 30% enzymatic concentration as solute and water as 70% solvent, the enzymatic concentration was calculated beforehand, for the tests, a completely randomized design with an AxBxC factorial arrangement with 2 repetitions was worked on. The factors studied are in (chicha preparation process: white, burned and wiwis), factor B (enzyme concentration: 0.05%, 0.10% and 15%) and C (cooking time: 40 minutes, 60 minutes and 80 minutes)....